PTPN11 induces endoplasmic stress and apoptosis in SH-SY5Y cells. (19th November 2017) - Chitranshi, Nitin; Dheer, Yogita; Gupta, Veer; Abbasi, Mojdeh; Mirzaei, Mehdi; You, Yuyi; Chung, Roger; Graham, Stuart L.; Gupta, Vivek
Highlights: Overexpression of PTPN11 (Shp2) promote TrkB dephosphorylation. AAV-mediated PTPN11 overexpression induces endoplasmic reticulum stress. Inhibition of PTPN11 under overexpression condition restores TrkB activity. AAV-mediated PTPN11 knockdown alleviates endoplasmic reticulum stress and promotes neurite outgrowth. Abstract: PTPN11 is associated with regulation of growth factor signaling pathways in neuronal cells. Using SH-SY5Y neuroblastoma cells, we showed that adeno-associated virus (AAV)-mediated PTPN11 upregulation was associated with TrkB antagonism, reduced neuritogenesis and enhanced endoplasmic reticulum (ER) stress response leading to apoptotic changes. Genetic knock-down of PTPN11 on the other hand leads to increased TrkB phosphorylation in SH-SY5Y cells . ER stress response induced by PTPN11 upregulation was alleviated pharmacologically by a TrkB agonist. Conversely the enhanced ER stress response induced by TrkB receptor antagonism was ameliorated by PTPN11 suppression, providing evidence of cross-talk of PTPN11 effects with TrkB actions. BDNF treatment of neuronal cells with PTPN11 upregulation also resulted in reduced expression of ER stress protein markers. This study provides evidence of molecular interactions between PTPN11 and the TrkB receptor in SH-SY5Y cells. The results reinforce the role played by PTPN11 in regulating neurotrophin protective signaling in neuronal cells and highlight that PTPN11 dysregulation promotes apoptotic activation. Based on these findings we suggest that blocking PTPN11 could have potential beneficial effects to limit the progression of neuronal loss in neurodegenerative disorders.